2014
DOI: 10.1126/scitranslmed.3009443
|View full text |Cite|
|
Sign up to set email alerts
|

The HMGB1-RAGE axis mediates traumatic brain injury–induced pulmonary dysfunction in lung transplantation

Abstract: Traumatic brain injury (TBI) results in systemic inflammatory responses that affect the lung. This is especially critical in the setting of lung transplantation where more than half of donor allografts are obtained postmortem from individuals with TBI. The mechanism by which TBI causes pulmonary dysfunction remains unclear but may involve the interaction of high mobility group box 1 (HMGB1) protein with the receptor for advanced glycation end products (RAGE). To investigate the role of HMGB1 and RAGE in TBI-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 68 publications
1
87
2
1
Order By: Relevance
“…4). RAGE deficiency leads to increased IL-10 production by T cells in vitro (37) as well as to increased IL-10 levels in murine models of hemorrhagic shock (38) and traumatic brain injury-induced pulmonary dysfunction (39) and in mice fed a high fat diet (40). Therefore, our finding of RAGE-dependent suppression of IL-10 production is consistent with the findings of others.…”
Section: Discussionsupporting
confidence: 82%
“…4). RAGE deficiency leads to increased IL-10 production by T cells in vitro (37) as well as to increased IL-10 levels in murine models of hemorrhagic shock (38) and traumatic brain injury-induced pulmonary dysfunction (39) and in mice fed a high fat diet (40). Therefore, our finding of RAGE-dependent suppression of IL-10 production is consistent with the findings of others.…”
Section: Discussionsupporting
confidence: 82%
“…This is likely reflective of the diverse heterogeneity in age, health status, cause of death, and other donor factors among our study cohort. Although traumatic injury has been shown to promote the release of DAMPs and to effect organ quality in previous studies (25,26,55), we found no associations between traumatic brain injury and levels of mtDNA or EAD in our cohort. However, we did identify a significant correlation between KDPI and the PMN-activating qualities of donor plasma, indicating that a donor's health status can affect their inflammatory state.…”
Section: Discussioncontrasting
confidence: 54%
“…Also, reducing the expression of iNOS can protect mice from ALI [32], demonstrating that these inflammatory mediators are essential to TBI-induced ALI. Conversely, the anti-inflammatory cytokine IL-10 is reported to protect mice from the inflammation process in TBI-induced ALI [33]. In the current study, we discovered that pHBSP ameliorated TBI-induced decrease of PaO 2 , and pHBSP significantly decreased TBI-induced up-regulation of TNF-α, IL-6, IL-1β and iNOS mRNA expression in the lung, while up-regulated the mRNA expression level of IL-10 in the lung.…”
Section: Discussionmentioning
confidence: 99%